2021
DOI: 10.1002/jmri.27651
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral and Peritumoral Radiomics Based on Functional Parametric Maps from Breast DCE‐MRI for Prediction of HER‐2 and Ki‐67 Status

Abstract: Background Radiomics has been applied to breast magnetic resonance imaging (MRI) for gene status prediction. However, the features of peritumoral regions were not thoroughly investigated. Purpose To evaluate the use of intratumoral and peritumoral regions from functional parametric maps based on breast dynamic contrast‐enhanced MRI (DCE‐MRI) for prediction of HER‐2 and Ki‐67 status. Study Type Retrospective. Population A total of 351 female patients (average age, 51 years) with pathologically confirmed breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 44 publications
8
54
3
Order By: Relevance
“…The ROC curve indicated that the com-rad-score yielded a higher AUC score than intra-and peri-rad-scores in both the training and validation cohorts. The results were in agreement with those of several recent studies, which indicated that a radiomics model including intra-and peritumoral features could improve the diagnostic performance for predicting the pathological outcome in BC [29,30,37].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The ROC curve indicated that the com-rad-score yielded a higher AUC score than intra-and peri-rad-scores in both the training and validation cohorts. The results were in agreement with those of several recent studies, which indicated that a radiomics model including intra-and peritumoral features could improve the diagnostic performance for predicting the pathological outcome in BC [29,30,37].…”
Section: Discussionsupporting
confidence: 92%
“…The features used to calculate the three rad-scores were mainly Law and Gabor features, which may reflect intra-and peritumor heterogeneity. Gabor features can detect the wavelike patterns of intensity variation across different spatial scales in different orientations, and Law features can capture the patterns of inconsistent enhancement and abnormal structure [26,29,31]. However, detailed intraand peritumor features are usually difficult to detect using the naked eye, whereas they can be easily detected by radiomics analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al found that the radiomics features extracted from the 3-mm peritumoral region could differentiate benign and malignant breast lesions on contrast-enhanced mammography (25). Li et al extracted intratumoral and 4-mm peritumoral radiomics features to predict the expression of HER2 and Ki-67 in breast cancer, and their models achieved good performance (26). In our study, 6 mm was determined as the optimal peritumoral size in tasks 1, 3, and 4, and 8 mm was determined as the optimal peritumoral size in task 2.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the radiomics features in the peritumoral areas based on various image types, such as mammography, ultrasound, and MRI, and had preliminary results in tumor diagnosis, biological indicator prediction, and prognosis evaluation (23)(24)(25). Li et al recently reported that the radiomics features in the intra-/peritumoral regions based on DCE-MRI are able to identify the HER2 and Ki-67 status in breast cancer (26). In Li's study, the peritumoral region was set as 4 mm from the tumor boundary; however, the optimal peritumoral size for breast cancer has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%